Refugees and citizens: Understanding Eritrean refugees' ambivalence towards homeland politics. (February 2019) - Belloni, Milena
This article revisits ambivalence as a protracted state which does not simply develop as a result of the migration experience but stems from overlapping levels of normative inconsistency. Drawing from my ethnography of Eritreans' everyday life in the homeland and abroad, I analyse their attitudes of patriotism and disenchantment through an ambivalence lens. Their ambiguous attitudes are arising from national and transnational Eritrean state policies and are further complicated by their role as "political refugees" in host countries. My informants' ambivalence stems from them embodying more than one role (i.e. patriots, family breadwinners, refugees from and citizens of their homeland), from contradictory expectations pertaining to the same role (i.e. young citizens in Eritrea) and from clashing implications of being members of two different social systems (i.e. the destination country and the country of origin). Thus, Eritreans' political loyalties and actions are characterised by a state of ambivalence throughout their migration process. Despite its peculiar characteristics, this case study sheds light on the complexity of ambivalence, as more than a temporary condition, for migrants and refugees in particular. In the current scenario of emigrant states' transnational governance, protracted ambivalence is likely to mark the attitudes of an increasing number of people on the move as both refugees from and citizens of their country of origin.